Reconsidering outdoor temperature and cognition in multiple sclerosis. (April 2016) - Roberg, Brandon L; Bruce, Jared M
Background: Research in multiple sclerosis (MS) suggests warmer weather plays a role in disease manifestation. Objective: This work sought to replicate the finding that warmer outdoor temperatures are significantly associated with poorer cognition in MS. Methods: Associations between outdoor temperature and cognition were examined in three studies with a total of 263 patients with MS. Results: Contrary to previous research, no significant relationship was found between cognitive performance and outdoor temperature in MS. Conclusions: The results of the current work underscore the need to better understand if, when, and how cognitive performance may be influenced by seasonal variables in MS.